Anti-Aging Performance and Action Mechanism of Asphalt Modified by Composite Modification - Zhisheng Liu; Xiaolong Sun; Hualong Xu; Yuanyu Lu; Zipeng Su; Yuanchang Ye; Guoxuan Huang (Applied Sciences)
In order to evaluate the effect and mechanism of composite modifiers on the anti-aging property of asphalt, this study selected hydrotalcite and ultraviolet absorber as anti-aging modifiers to prepare different types of modified asphalt and carry out ultraviolet aging treatment. The effects of composite modification on the physical and rheological properties of asphalt under ultraviolet aging conditions were studied by three indices and by dynamic shear rheometer. The distribution and interaction characteristics of composite modifiers in asphalt matrix were analyzed by scanning electron microscopy (SEM) and energy dispersion spectroscopy (EDS). Fourier transform infrared spectroscopy (FTIR) was used to analyze the changes in functional groups and characteristic parameters in the compound modified asphalt. Based on this, a molecular dynamics model of the compound modified asphalt was constructed, and the changes in solubility parameters, free volume, and mean azimuth shift were analyzed. The results show that the addition of the compound modifier can significantly improve the UV aging resistance of asphalt, mainly by controlling the asphalt components and characteristic functional groups, and the good compatibility between the modifier and asphalt ensures the modification effect.